Perceptions among paddy farmers towards usage of MR220CL at Parit 4,Sungai Burong, Tanjung Karang, Selangor / Zuazlina Zulkefly - Zulkefly, Zuazlina (Faculty of Plantation and Agrotechnology, 2016)
Rice is one of the real sustenance hotspot for more than half of the populace on the planet (Gealy et aI., 2003) and it is the third most critical product in Malaysia (Karim et aI., 2004). Nowadays, the current issue in rice production is to ensure the sustainable production of rice. The study aim is to investigate the perception among paddy farmers on the usage of MR220CL at Parit 4, Sungai Burong, TanjungKarang, Selangor. Research method by questionnaires and interview were involving 217 respondents. The results represented by using factor analysis. The result revealed that the three factors which are prior knowledge, behavioral attitude and factors affecting the usage of MR220CL contributed to the perception of farmers. Based on the result obtained farmers seemed to have knowledge and experiences regarding planting management also in paddy variety. However, they somehow did not follow some of the recommendation by the extension agents as they only focused in obtaining high yield with no concern on the consequences they might be facing in future. Thus, the farmers should attend more courses and seminars held by the agriculture department or any extension agents in order to gain more knowledge and get better view in future on the drawbacks of bad practices management.